GlSch: Observation Scheduler for the GLORIA Telescope Network - López Casado, Carmen; Pérez-del-Pulgar-Mancebo, Carlos Jesús; Muñoz-Martínez, Víctor Fernando; Castro-Tirado, Alberto J. (My University, 2017)
This paper proposes the design and development of a scheduler for the GLORIA telescope network. This network, which main objective is to make astronomy closer to citizens in general, is formed by 18 telescopes spread over four continents and both hemispheres. Part of the management of this network is made by the network scheduler. It receives the observation requests made by the GLORIA users and then sends it to the most suitable telescope. A key module of the network scheduler is the telescope decision algorithm that makes possible to choose the best telescope, and thus avoiding offering an observation to a telescope that cannot execute it. This paper shows two different telescope decision algorithms: the first one is only based on weather forecast, meanwhile the second one uses fuzzy logic and information from each network telescope. Both algorithms were deployed in the GLORIA network. The achieved results coupled with a comparative of their performance is shown. Moreover, the network scheduler architecture, based on a hybrid distributed-centralized schema, is detailed.
Keywords: Astronomía -- Aparatos e instrumentos - Programas de ordenador; Astronomy; Telescope network; Scheduler algorithm; Fuzzy logic; Software